Advances in Transition‐Metal‐Catalysed Alkyne Hydroarylations. Issue 4 (2nd June 2016) - Biffis, Andrea; Tubaro, Cristina; Baron, Marco
Abstract: We present herein a personal account of our achievements in the development of novel catalytic systems based on late‐transition‐metal complexes for the hydroarylation of alkynes. In particular, our targets were intermolecular hydroarylation reactions with arene or heteroarene substrates devoid of directing groups. We have shown that complexes of palladium, platinum or gold with N‐heterocyclic carbene (NHC) ligands can be particularly useful catalysts for this reaction; the NHC ligand imparts greater stability to the complex and renders the catalytic system more productive. Furthermore, we have identified promoters and reaction media that allow to significantly improve the catalytic activity under mild conditions, to control the reaction chemoselectivity and to steer it towards more complex products; thus making this reaction considerably more attractive for the synthetic chemist. Abstract : Cheaper control : An overview of achievements in the application of late‐transition‐metal complexes as catalysts for the intermolecular hydroarylation of alkynes is presented herein. The usefulness of complexes of Pd, Pt, or Au with N‐heterocyclic carbenes (NHCs), in which the ligand stabilizes the complex and renders the catalytic system more productive, is highlighted. Promoters and reaction media for improved catalytic activity and control of the reaction chemoselectivity are also discussed.